Weed Control in Beans and Peas (Bush, Pole, Lima Beans, English Peas, and Southern Peas) - William M. Stall (EDIS, 2010)
Revised! HS188, a 5-page fact sheet by William M. Stall, provides updated recommendations for weed control in beans and peas. Published by the UF Department of Horticultural Sciences, March 2010.